A One‐Structure‐Based Hybridized Nanogenerator for Scavenging Mechanical and Thermal Energies by Triboelectric–Piezoelectric–Pyroelectric Effects. Issue 15 (18th February 2016) - Wang, Shuhua; Wang, Zhong Lin; Yang, Ya
Abstract : A hybridized nanogenerator is demonstrated, which has the structure of PVDF nanowires–PDMS composite film/indium tin oxide (ITO) electrode/polarized PVDF film/ITO electrode, and which can individually/simultaneously scavenge mechanical and thermal energies using piezoelectric, triboelectric, and pyroelectric effects. As compared with the individual energy harvesting unit, the hybridized nanogenerator has a much better charging performance. This work may push forward a significant step toward multienergy harvesting technology.